On Cauchy–Pompeiu’s Operator in Octant Ring - Hasan Baddour; Anas Kar (Journal of Mathematics)
In this study, we have determined Cauchy–Pompeiu representation formula in octant unit ring R4 by modulation the main Cauchy–Pompeiu representation; this modulation was obtained by applying the parqueting-reflection method. Moreover, the boundedness of the modulated Cauchy–Pompeiu’s operator in R4 is proved by applying Schmitz’s inequality.